Rapid manufacturing : an industrial revolution for the digital age. - Hopkinson, N., ....-; Dickens, P. M., ....-; Hague, R. J. M., ....- (Chichester : Wiley, 2006)
Design. 1. Introduction to Rapid Manufacturing (Neil Hopkinson, Richard Hague and Phill Dickens). 2. Unlocking the Design Potential for Rapid Manufacturing (Richard Hague). 3. Customer Input and Customisation (Ian Campbell). 4. CAD and Rapid Manufacturing (Rik Knoppers). Materials and Processes. 5. Emerging Rapid Manufacturing Processes (Neil Hopkinson and Phill Dickens). 6. Materials Issues in Rapid Manufacturing (Dave Bourell). 7. Functionally Graded Materials (Poonjolai Erasenthiren). 8. Materials and Process Control for Rapid Manufacturing (Tim Gornet). 9. Production Economics of Rapid Manufacturing (Neil Hopkinson). Management. 10. Management and Implementation of Rapid Manufacturing (Richard Hague and Chris Tuck). Applications 11. Medical Applications (Russ Harris and Monica Savalani). 12. Rapid Manufacturing in the Hearing Industry (Martin Masters, Therese Velde and Fred McBagonluri). 13. Automotive Applications (Graham Tromans). 14. Rapid Manufacture in the Aeronautical Industry (Brad Fox). 15. Aeronautical Case Studies Using Rapid Manufacturing (John Wooten). 16. Space Applications (Roger Spielman). 17. Rapid Manufacturing for the Construction Industry (Rupert Soar). 18. Rapid Manufacturing for the Retail Industry (Janne Kyttanen).
Keywords: Productieprocessen; Rapid prototyping